Change of jurisdiction by the prosecutor: problems of law enforcement (Law and Safety, 2022)
The novelties of the criminal procedural legislation regarding the expansion of the grounds for the prosecutor to change the jurisdiction of criminal offenses have been analyzed. It has been established that in the conditions of martial law, liability as one of the general provisions of pre-trial investigation has lost its primary categorical meaning, the essence of which is to determine the competence of the pre-trial investigation body based on the set of legally established features of criminal proceedings. With the application of the comparative method, an analysis of the powers of the prosecutor regarding their change of liability in criminal offenses with the beginning of the military aggression of the Russian Federation before and after the entry into force of the amendments to Part 5 of Article 36 of the CCP of Ukraine has been carried out. It has been recognized that in the conditions of martial law, each body of pre-trial investigation is universal through the prism of the institution of accountability, since pre-trial investigation can be carried out in any criminal offense by the decision of the authorized prosecutor.The general conditions for the prosecutor to make a decision on the change of jurisdiction have been highlighted: the authorized subject; form of procedural decision; the subject of a procedural decision; legal grounds. With the help of the forecasting method, the problems of law enforcement that may occur in the event that the prosecutor entrusts the pre-trial investigation of a criminal offense to a pre-trial investigation body that does not specialize in the investigation of this category of criminal proceedings have been determined. The ways of improving the criminal procedural legislation regarding the normalization of the provisions of the criminal procedural legislation regarding the prosecutor's discretionary powers when determining the pre-trial investigation body entrusted with the pre-trial investigation of a criminal offense have been outlined. The position of the judge of the Criminal Court of Cassation as part of the Supreme Court and other scientists was supported regarding the need to introduce judicial control over the justification and motivation of the prosecutor's decision to entrust the pretrial investigation of any criminal offense to another pretrial investigation body.
Keywords: criminal proceedings; criminal offense; pretrial investigation body; prosecutor; investigation.